A Green Desulfurization Technique: Utilization of Flue Gas SO2 to Produce H2 via a Photoelectrochemical Process Based on Mo-Doped BiVO4 - Han, Jin; Li, Kejian; Cheng, Hanyun; Zhang, Liwu (Frontiers in Chemistry, 2017)
A green photoelectrochemical (PEC) process with simultaneous SO2 removal and H2 production has attracted an increasing attention. The proposed process uses flue gas SO2 to improve H2 production. The improvement of the efficiency of this process is necessary before it can become industrial viable. Herein, we reported a Mo modified BiVO4 photocatalysts for a simultaneous SO2 removal and H2 production. And the PEC performance could be significantly improved with doping and flue gas removal. The evolution rate of H2 and removal of SO2 could be enhanced by almost 3 times after Mo doping as compared with pristine BiVO4. The enhanced H2 production and SO2 removal is attributed to the improved bulk charge carrier transportation after Mo doping, and greatly enhanced oxidation reaction kinetics on the photoanode due to the formation of SO32- after SO2 absorption by the electrolyte. Due to the utilization of SO2 to improve the production of H2, the proposed PEC process may become a profitable desulfurization technique.